2021
DOI: 10.1161/circoutcomes.120.007641
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Machine-Learning Algorithm in the Electronic Health Record for Targeted Screening for Familial Hypercholesterolemia: A Quality Improvement Study

Abstract: GOALS AND VISION OF THE PROGRAMFamilial hypercholesterolemia (FH) is a lipid disorder that results in elevated serum LDL (low-density lipoprotein) cholesterol and markedly increased cardiovascular risk. 1,2 Classical observational data suggest that prevalence of heterozygous FH is ≈1:250, and it is estimated that only 10% of patients with FH in the United States have been diagnosed. 1,2 Early and timely diagnosis of FH reduces cardiovascular risk, which heightens the need for targeted screening. 2,3 To increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The algorithm based on data learning can not only learn the feature detector like Quarknetworks, but also learn the feature descriptor. With the improvement of machine learning [20][21][22][23][24], Simoserra et al proposed Deepdesc [25] for key point descriptor learning. This method uses a convolutional neural network to learn the discriminant representation of image blocks (patches), trains a Siamese network with paired inputs, and processes a large number of paired image blocks by combining the random extraction of training sets and the mining strategy for patch pairs that are difficult to classify.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm based on data learning can not only learn the feature detector like Quarknetworks, but also learn the feature descriptor. With the improvement of machine learning [20][21][22][23][24], Simoserra et al proposed Deepdesc [25] for key point descriptor learning. This method uses a convolutional neural network to learn the discriminant representation of image blocks (patches), trains a Siamese network with paired inputs, and processes a large number of paired image blocks by combining the random extraction of training sets and the mining strategy for patch pairs that are difficult to classify.…”
Section: Introductionmentioning
confidence: 99%
“…They found that 87% and 77% of the individuals were classified as probable or definite FH, respectively, demonstrating the accuracy and efficiency of the model. In an observational study, Sheth et al prospectively implemented the FIND FH model to screen for FH ( 21 ). Based on EHRs from the University of Pennsylvania Healthcare System ( n = 1,607,606), there were 8,614 patients with a FIND FH score >0.2, suggesting possible FH.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 The study findings were also part of a larger research plan to deploy the algorithm to directly improve patient care in a large healthcare system. 53…”
Section: Discussionmentioning
confidence: 99%